Frontline Turkey : the conflict at the heart of the Middle East - Başaran, Ezgi, 1981- 1981- (I.B. Tauris, 2017)
Turkey is on the front line of the war which is consuming Syria and the Middle East. Its role is complicated by the long-running conflict with the Kurds on the Syrian border - a war that has killed as many as 80,000 people over the last three decades. In 2011 President Erdogan promised to make a deal with the PKK (Kurdistan Workers' Party), but the talks marked a descent into assassinations, suicide bombings and the killing of civilians on both sides. The Kurdish peace process finally collapsed in 2014 with the spillover of the Syrian civil war. With ISIS moving through northern Iraq, Turkey has declared war on Western allies such as the Kurdish YPG (People's Protection Unit) - the military who rescued the Yezidis and fought with US backing in Kobane. Frontline Turkey shows how the Kurds' relationship with Turkey is at the very heart of the Middle Eastern crisis, and documents, through front-line reporting, how Erdogan's failure to bring peace is the key to understanding current events in Middle East